Reinforcement of electrospun poly(ε‐caprolactone) scaffold using diopside nanopowder to promote biological and physical properties - Hosseini, Yasamin; Emadi, Rahmatollah; Kharaziha, Mahshid; Doostmohammadi, Ali (Journal of applied polymer science, 2017)
ABSTRACT Considerable efforts have been devoted toward the development of electrospun scaffolds based on poly(ε‐caprolactone) (PCL) for bone tissue engineering. However, most of previous scaffolds have lacked the structural and mechanical strength to engineer bone tissue constructs with suitable biological functions. Here, we developed bioactive and relatively robust hybrid scaffolds composed of diopside nanopowder embedded PCL electrospun nanofibers. Incorporation of various concentrations of diopside nanopowder from 0 to 3 wt % within the PCL scaffolds notably improved tensile strength (eight‐fold) and elastic modulus (two‐fold). Moreover, the addition of diopside nanopowder significantly improved bioactivity and degradation rate compared to pure PCL scaffold which might be due to their superior hydrophilicity. We investigated the proliferation and spreading of SAOS‐II cells on electrospun scaffolds. Notably, electrospun PCL‐diopside scaffolds induced significantly enhanced cell proliferation and spreading. Overall, we concluded that PCL‐diopside scaffold could potentially be used to develop clinically relevant constructs for bone tissue engineering. However, the extended in vivo studies are essential to evaluate the role of PCL‐diopside fibrous scaffolds on the new bone growth and regeneration. Therefore, in vivo studies will be the subject of our future work. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 44433.